Economic effects of covid-19 on the hotel industry in Quito - Funes Samaniego, Liliana Alejandra; Peña Guillén, Jesús Alberto (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
This article seeks to analyze the economic effects of COVID-19 in the hotel industry in Quito considering that, as of February 2020, the first case was detected, however; its effect began to be observed in March 2022, generating a significant decrease in the arrival of tourists to Quito, affecting the hotel industry and the economy of its actors that comprise it; for which the trend of the years 2007 to 2019 was analyzed through the application of a time series model with intervention allowing to predict the behavior of the arrival of tourists to Quito during the last quarter of 2022 and the entire year 2023; With the applied methodology, robust results are obtained, indicating that the SARIMA(1,1,1)(2,0,0,)[12] model with intervention generates the most reliable estimates under the effect of COVID-19 for the last quarter 2022 and the entire year 2023, concluding the different trends generated with the analysis of the data corresponding to the arrival of tourists to Quito between the years 2019 and 2022.